Pengaruh Influencer Marketing dan Word of Mouth terhadap Keputusan Pembelian Produk Kosmetik (Sunscreen Azarine) di Meulaboh, Aceh Barat - Fadli, Muhammad; Putri, Cut Mega; Muzakir, Muzakir (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Influencer Marketing and Word of mouth on purchasing decisions for Azarine Sunscreen products among Generation Z in Meulaboh, West Aceh. The research is motivated by the increasing digital activity among young consumers, which significantly affects purchasing behavior, particularly in skincare products. This research employs a quantitative associative approach using a questionnaire as the primary data collection instrument. The sample consists of 100 respondents who are Generation Z consumers domiciled in Meulaboh and have experience or interest in Azarine Sunscreen products, obtained through Online data Keyand reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that partially, Influencer Marketing and Word of mouth have a positive and significant effect on purchasing decisions for Azarine Sunscreen products. Simultaneously, both variables also have a significant influence on purchasing decisions. These findings support Source Credibility Theory, Trust Theory, and Consumer Purchase Decision Theory, which explain that consumer purchasing behavior is influenced by source credibility, trust, and information evaluation processes in digital environments. Therefore, this study contributes both theoretically and practically by providing insights for skincare businesses in developing more effective digital marketing strategies and strengthening consumer trust in the digital era.